Feature Requirement With Human-Centered Design Approach to Developing A Psychological-Based HIV - Dia Bitari Mei Yuana; Afis Asryullah Pratama; Tegar Wahyu Yudha Pratama; Nilam Puspitasari; Nurina Aprilya; Faiqatul Hikmah; Bayu Krisna Dwihadi Fahrizal (International Journal of Healthcare and Information Technology, 2026)
HIV cases among adolescents in Indonesia have been on the rise recently. Moderate to severe depressive symptoms are reported to be experienced by adolescents living with HIV, which coincides with this increase in cases. This suggests that it is essential to initiate strategic initiatives to enhance the efficacy of the initial screening process by implementing application-based HIV risk group identification through the use of psychological approaches. Designing a user interface that is appropriately structured and meets user requirements is crucial to ensuring the effectiveness of the application being developed. This investigation involved the assessment of feature requirements by HIV disease counselors and psychologists in accordance with the Human-Centered Design (HCD) methodology. Counselors who specialize in HIV disease contribute to the query elements utilized in the initial screening assessment. Meanwhile, psychologists contribute to the approval of the questions utilized as an initial screening test, which affects the psychological well-being and accuracy of adolescent users. The stages adopted for the implementation of HCD were modified in accordance with ISO 9241-210. This research generated user personas, use case diagrams, and the User Interface (UI) design for the VitaMind application, which is primarily designed for pre-test screening. This is a multiplatform application that comprises both web-based and mobile components. This application design has been tested using the system usability scale (SUS) method and produced an accuracy score of 86.1%. The primary contribution and novelty of this research lies in the application of Human-Centered Design principles to the development of a mental health-focused, pre-test HIV screening application tailored for students. Usability testing, employing the System Usability Scale (SUS) method, yielded results demonstrating a high degree of usability.